Development of a novel electroless deposited nickel braze for micro-tubular solid oxide fuel cell current collector contacting - O. Hodjati-Pugh; A. Dhir; R. Steinberger-Wilckens (Journal of Advanced Joining Processes, 2021)
A brazing process for the fuel electrode (anode) contacting of a micro-tubular fuel cell is reported. The low-cost, novel, electroless deposited braze suitable for mass production was optimised with respect to material loading and brazing environment. Durable current collector-anode joints were obtained while protecting sensitive solid oxide fuel cell components. It was determined that a minimum braze loading of 20 µm thickness was required to join the current collector at multiple contacts along the interior tube wall. The final brazed current collector design achieved a high peak power density of 0.14 W.cm−2 at 750°C, 2.35 times higher than for the un-brazed design.